Efficacy and safety of eight types Salvia miltiorrhiza injections in the treatment of unstable angina pectoris: A network meta-analysis - Li, Mingxuan; Li, Hongdian; Liu, Hongxu; Lai, Xiaolei; Xing, Wenlong (Frontiers in Pharmacology, 2022)
Background Salvia miltiorrhiza injection classes（SMIC）is widely used in the treatment of unstable angina (UA）. However, it is uncertain which SMIC is more effective in terms of UA efficacy. The purpose of this Network Meta-analysis (NMA) was to compare the treatment effects of various SMICs to determine the best SMIC for the treatment of UA. Methods. The Chinese Journal Full Text Database (CNKI), Wanfang Database, Chinese Science and Technology Journal Full Text Database (VIP), Chinese Biomedical Literature Database (CBM), PubMed, Web of Science, and Cochrane Library databases were searched to screen randomized controlled trials (RCTs) of SMIC for UA. The searchtime frame was all from the establishment of the database to May 2022. RevMan 5.3 and Stata 14.0 software were used to prior to the systematic review and network meta-analysis. Results. A total of 148 studies including 14979 patients, including 7584 cases in the experimental group and 7395 cases in the control group were included, and eight SMIC were extracted, namely, Danshen injection, Fufang Danshen injection, Guanxinning injection, Danshenchuanxiongqin injection, Danhong injection, Danshentong IIA Huangsuanna injection, Shenxiong Putaotang injection ,and Danshenduofensuanyan injection. The results of the reticulated meta-analysis showed that，In terms of total effective rate, Shenxiong Putaotang injection and Danshenchuanxiongqin injection have the advantage；In terms of ECG efficiency, Danshentong IIA Huangsuanna injection and Danshen injection have an advantage；Danshenchuanxiongqin injection and Danshenduofensuanyan injection were more effective than other SMICs in improving angina pectoris attacks；Shenxiong Putaotang injection has an advantage in improving hs-CRP；Shenxiong Putaotang injection and Danshentong IIA Huangsuanna injection have advantages in improving TC and TG, respectively. Conclusion. The eight SMICs included in the current study were effective in treating UA，Shenxiong Putaotang injection and Danshentong IIA Huangsuanna injection were both superior in improving all outcome indicators. However, there is still a need for larger samples and high-quality randomized controlled trials for more refined comparisons of various SMICs.